A new soft red winter wheat cultivar 'GA 08535‐15LE29' adapted to Georgia and the U.S. southeast region. Issue 3 (28th May 2022) - Mergoum, Mohamed; Johnson, Jerry; Buck, James; Buntin, G. David; Sutton, Steve; Lopez, Benjamin; Mailhot, Daniel; Chen, Zhenbang; Bland, Dan; Harrison, Stephen; Murphy, Joseph Paul; Mason, Esten; et al.
Abstract: Soft red winter wheat (SRWW) ( Triticum aestivum L.) production in the southeastern United States is affected by biotic and abiotic stresses that can result in yield losses and reduced acreage. Developing new cultivars with high yield, good resistance to predominant pests, and acceptable quality to maximize value in regional markets is needed. The University of Georgia (UGA) SRWW breeding program, in collaboration with institutions in the region including the Southern UNiversities GRAINS (SUNGRAINS) programs, is responding to these challenges by developing and releasing superior cultivars adapted to the region. 'GA 08535‐15LE29' (Reg. no. CV‐1191, PI 693269) SRWW cultivar was developed and released by the UGA College of Agricultural and Environmental Sciences and licensed to Uni South Genetics seed company in 2018 as USG 3640. GA 08535‐15LE29 is well adapted to Georgia and the U.S. southeast region with high yield and good resistance to leaf ( Puccinia triticina Erikss.) and stripe ( P. striiformis Westend.) rusts, Fusarium head blight (caused by Fusarium graminearum Schwabe), powdery mildew ( Erisyphe graminis ), and Soil‐borne wheat mosaic virus (SBWMV) diseases. GA 08535‐15LE29 showed moderate field resistance to Hessian fly [ Mayetiola destructor (Say)]. GA 08535‐15LE29 has Sbm1 and Yr17/Lr37/Sr38 for resistance to SBWMV and rust diseases and has good grain volume weight and acceptable milling and baking qualities. Core Ideas: GA 08535‐15LE29 was developed by the University of Georgia in collaboration with SUNGRAINS. GA 08535‐15LE29 is well adapted to Georgia and the U.S. Southeast. GA 08535‐15LE29 is resistant to prevalent diseases (e.g., rusts) and insects (e.g., Hessian fly). GA 08535‐15LE29 possesses Sbm1 and Yr17/Lr37/Sr38 genes/QTL.